2007
DOI: 10.1080/01904160701628908
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effect on Growth Parameters and Macronutrient Use of Sweet Pepper

Abstract: Sweet pepper plants (Capsicum annuum L.) grown under greenhouse conditions differed widely in the rate of production of their total dry mass and their harvestable weight, although there was not shortage in water or nutrient supply. Plants were grown in aerated nutrient solutions along two different growing seasons. The differences in plant productivity were mainly due to the environmental conditions of the growth cycle. During the increasing day length season, from the beginning of spring to summer (13.0 to 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…Therefore, this provides a robust way to predict the aerial DM of the plant at any plant stage of the crop cycle. Our values of LUE are higher than those obtained by Prieto et al (2007) (0.42 g/MJ) but similar to those of Dorais (2003) (1.0 g/MJ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, this provides a robust way to predict the aerial DM of the plant at any plant stage of the crop cycle. Our values of LUE are higher than those obtained by Prieto et al (2007) (0.42 g/MJ) but similar to those of Dorais (2003) (1.0 g/MJ).…”
Section: Resultssupporting
confidence: 81%
“…Additionally, a reduction of the sum of intercepted radiation of 4.8% was observed. Under a Mediterranean climate, Prieto et al (2007) obtained less leaf area in hydroponic culture (54% lower compared with our plants grown in CC). In similar cultivars and plant cultures, Assouline et al (2006) obtained values of leaf area index (4.3 m 2 Ám -2 ) slightly higher than ours.…”
Section: Resultscontrasting
confidence: 56%
“…Higher LA accelerates the production of metabolites. Prieto et al (2007) stated that higher LA resulted in an increase in the plant's ability to intercept light. The higher the growth parameter i.e.…”
Section: Physiological Growth Analysismentioning
confidence: 99%
“…This may explain sugar accumulation in fruits grown in higher radiation. A high positive correlation between radiation and dry matter content in pepper fruits was observed by Prieto et al (2007). In addition, a high light intensity increased sugar concentration in pepper (Caruso et al 2004).…”
Section: Discussionmentioning
confidence: 92%
“…Different results were reported by Caruso et al (2004), who observed a reduction of nitrates in pepper at better light conditions. According to Prieto et al (2007), higher light intensity could stimulate the accumulation of nitrogen in pepper. Lower ammonium content in pepper fruits in the case of higher radiation was also observed in the presented experiment.…”
Section: Discussionmentioning
confidence: 98%